background image

14.1. ORDERING OF FILTERS

244

14.1.1. Existence of no more than one monovalued injective reloid

for a given pair of ultrafilters.

14.1.1.1.

The lemmas.

The lemmas in this section were provided to me by

Robert Martin Solovay

in [

39

]. They are based on

Wistar Comfort

’s work.

In this section we will assume

µ

is an ultrafilter on a set

I

and function

f

:

I

I

has the property

X

µ

f

1

X

µ

.

Lemma

1295

.

If

X

µ

then

X

∩ h

f

i

X

µ

.

Proof.

If

h

f

i

X /

µ

then

X

f

1

h

f

i

X /

µ

and so

X /

µ

. Thus

X

µ

∧ h

f

i

X

µ

and consequently

X

∩ h

f

i

X

µ

.

We will say that

x

is

periodic

when

f

n

(

x

) =

x

for some positive integer

x

. The

least such

n

is called

the period

of

x

.

Let’s define

x

y

iff there exist

i, j

N

such that

f

i

(

x

) =

f

j

(

y

). Trivially it

is an equivalence relation. If

x

and

y

are periodic, then

x

y

iff exists

n

N

such

that

f

n

(

y

) =

x

.

Let

A

=

n

x

I

x

is periodic with period

>

1

o

.

We will show

A /

µ

. Let’s assume

A

µ

.

Let a set

D

A

contains (by the axiom of choice) exactly one element from

each equivalence class of

A

defined by the relation

.

Let

α

be a function

A

N

defined as follows. Let

x

A

. Let

y

be the unique

element of

D

such that

x

y

. Let

α

(

x

) be the least

n

N

such that

f

n

(

y

) =

x

.

Let

B

0

=

n

x

A

α

(

x

) is even

o

and

B

1

=

n

x

A

α

(

x

) is odd

o

.

Let

B

2

=

n

x

A

α

(

x

)=0

o

.

Lemma

1296

.

B

0

∩ h

f

i

B

0

B

2

.

Proof.

If

x

B

0

∩ h

f

i

B

0

then for a minimal even

n

and

x

=

f

(

x

0

) where

f

m

(

y

0

) =

x

0

for a minimal even

m

. Thus

f

n

(

y

) =

f

(

x

0

) thus

y

and

x

0

laying in

the same equivalence class and thus

y

=

y

0

. So we have

f

n

(

y

) =

f

m

+1

(

y

). Thus

n

m

+ 1 by minimality.

x

0

lies on an orbit and thus

x

0

=

f

1

(

x

) where by

f

1

I mean step backward

on our orbit;

f

m

(

y

) =

f

1

(

x

) and thus

x

0

=

f

n

1

(

y

) thus

n

1

m

by minimality

or

n

= 0.

Thus

n

=

m

+ 1 what is impossible for even

n

and

m

. We have a contradiction

what proves

B

0

∩ h

f

i

B

0

⊆ ∅

.

Remained the case

n

= 0, then

x

=

f

0

(

y

) and thus

α

(

x

) = 0.

Lemma

1297

.

B

1

∩ h

f

i

B

1

=

.

Proof.

Let

x

B

1

∩ h

f

i

B

1

. Then

f

n

(

y

) =

x

for an odd

n

and

x

=

f

(

x

0

)

where

f

m

(

y

0

) =

x

0

for an odd

m

. Thus

f

n

(

y

) =

f

(

x

0

) thus

y

and

x

0

laying in

the same equivalence class and thus

y

=

y

0

. So we have

f

n

(

y

) =

f

m

+1

(

y

). Thus

n

m

+ 1 by minimality.

x

0

lies on an orbit and thus

x

0

=

f

1

(

x

) where by

f

1

I mean step backward

on our orbit;

f

m

(

y

) =

f

1

(

x

) and thus

x

0

=

f

n

1

(

y

) thus

n

1

m

by minimality (

n

= 0

is impossible because

n

is odd).

Thus

n

=

m

+ 1 what is impossible for odd

n

and

m

. We have a contradiction

what proves

B

1

∩ h

f

i

B

1

=

.

Lemma

1298

.

B

2

∩ h

f

i

B

2

=

.

Proof.

Let

x

B

2

∩ h

f

i

B

2

. Then

x

=

y

and

x

0

=

y

where

x

=

f

(

x

0

). Thus

x

=

f

(

x

) and so

x /

A

what is impossible.